Televised Influence: Examining Opinion Formation Through Live Completion of a Voting Advice Application - Ioannidis, Nikandros; Triga, Vasiliki (My University, 2026)
The influence of candidate cues on voters’ opinion formulation is a subject of ongoing debate in political science. This study examines the 2023 Cyprus presidential elections, when the leading candidates completed the country’s most popular voting advice application live on national television. This unprecedented event created a natural experiment to test how televised disclosure of candidate positions affects alignment between voters and their preferred candidates. Drawing on voting advice application responses across a wide set of policy questions and employing regression discontinuity in time models, we estimate changes in voter–candidate congruence before and after the broadcast. The results show no uniform effect. For Andreas Mavroyiannis, supporters converged toward his progressive and pro-solution profile, particularly on foreign policy, welfare, and Cyprus settlement questions. For Averof Neophytou and Nikos Christodoulides, congruence did not increase consistently; in some cases, divergence emerged, as explicit cues exposed divisions within their heterogeneous or ambivalent coalitions. The findings provide mixed support for the expectation that cues strengthen congruence only on less entrenched issues. Convergence was most evident on novel questions, but divergence also occurred on identity and Cyprus-related issues. The study highlights that candidate cues can foster alignment but can also generate divergence, depending on candidate characteristics, issue polarisation, and coalition heterogeneity.
Keywords: candidate cues; elite influence; public opinion; voting advice applications; voter–candidate congruence